Expanding Definition of Technology in Special Education: Impact of Training on the Adoption of iPad Tablets by Special Educators. Issue 2 (4th March 2022) - Moreno, Gerardo
ABSTRACT: The role of technology in special education has increased over the last 20 years. Expedited by the introduction of Apple iPad and its implementation of touch-based input, the perception of technology has grown from a functional role for students with disabilities to a bridge in accessing general education curriculum. However, quality adoption of new technology within the classroom relies heavily on professional development of the special educator. This paper offers a discussion on the expansion of technology in special education, various attributes associated with quality educator training on technology, and the results of a five-year investigation on the formal training of special educators using iPad tablets. Results indicated longitudinal training focused on active learner experiences had a significant effect on the likelihood of special educator iPad tablet adoption and the resulting implementation in the classroom. Recommendations on educator professional training on iPad tablets follows results.